2018
DOI: 10.3855/jidc.10429
|View full text |Cite
|
Sign up to set email alerts
|

Brucellar terminal ileitis and epididymo-orchitis in an adolescent; case report and review of the literature

Abstract: Although brucellosis is a multi-systemic illness, terminal ileitis or colitis due to brucellosis is reported anecdotal in literature. Genitourinary manifestations of Brucella, namely epididymo-orchitis is very rare in childhood brucellosis. Herein, we present a case of brucellosis in a child with a rare combination of terminal ileitis and epididymo-orchitis not reported previously in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…3 In humans, Brucellosis can be produced by B. abortus, B. melitensis, B. suis biotypes 1-4 and sometimes by B. canis or Brucella of marine mammals, B. ovis, B. neotomae are also pathogenic to humans. 4 Incubation ranges goes from one to four weeks to several months. Systemic infection has clinical manifestations ranging from asymptomatic to fatal complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In humans, Brucellosis can be produced by B. abortus, B. melitensis, B. suis biotypes 1-4 and sometimes by B. canis or Brucella of marine mammals, B. ovis, B. neotomae are also pathogenic to humans. 4 Incubation ranges goes from one to four weeks to several months. Systemic infection has clinical manifestations ranging from asymptomatic to fatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Colitis and ileitis have been reported as rare sporadic cases in the literature. 4 In a meta-analysis of the neglected tropical diseases that included 57 articles related to the most frequent manifestations of brucellosis and that included 12 countries, it concluded that the abdominal manifestations were pain, splenomegaly and hepatomegaly with estimated overall proportions of 19%, 26% and 23% respectively. The number of studies that reported the presence of hepatitis was small, only seven in total, with an estimated 4% of patients affected in general.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde bruselloza bağlı kolit ve ileit vakaları da bildirilmiştir. Ancak bu tutulumlar oldukça seyrektir [46][47][48][49][50][51][52][53][54][55]. Bu tür mide-bağırsak lezyonları ilk olarak 1934'te otopsi serilerinde tanımlanmamıştır.…”
Section: Koli̇t İlei̇t Ve Di̇verti̇küli̇tunclassified
“…Oğuz ve ark. [48] terminal ileitis ve epididimo-orşiti olan bir çocuk hasta bildirmiştir. Ho ve ark.…”
Section: Koli̇t İlei̇t Ve Di̇verti̇küli̇tunclassified
“…In some pastoral systems, women have less access to information on disease prevention, especially regarding zoonosis, when compared to men (Oluka et al 2005;Mupawaenda et al 2009;Njuki and Sanginga 2013). As a zoonotic disease, brucellosis affects both men and women (D'anastasio et al 2011;Oguz and Oztek-Celebi 2018), with animals as the main source and reservoir of the disease (Godfroid et al 2011). Common symptoms of brucellosis in humans are undulant fever, weakness, joint pains and arthritis (Zhe Liu et al 2020).…”
Section: Introductionmentioning
confidence: 99%